Children’s Fundamental Movement Skills, Social Emotional Development and Physical Activity Development Based on Kids’ Athletics Intervention: SEM Modelling and Analysis - Huang, Chenhua; Choosakul, Chairat (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to examine the developmental status of fundamental movement skills, social emotional development, and physical activity in Chinese children aged 7 to 10. Using the Kids’ Athletics intervention, Structural Equation Modeling (SEM) was applied to analyze their developmental trajectories. Materials and methods. The study was conducted between April and June 2024, and involved 305 primary school students. The Children’s Fundamental Movement Skills Test, the Physical Activity Level Questionnaire for Children and Adolescents (ages 7-18), and the Student Social Emotional Competence Questionnaire were used to perform this study. SEM was applied to explore relationships among these developmental domains. Results. In post-intervention period, significant improvements were noted in fundamental movement skills, social emotional competence, and physical activity levels (all p < 0.05). The experimental group outperformed the control group in most metrics, except balance beam walking and the others’ perception dimension (p < 0.05). The structural model indicated an adequate fit, with path correlation analysis revealing a significant negative correlation between fundamental movement skills and social emotional development (r = -0.33, p < 0.001) and physical activity (r = -0.24, p < 0.001). Furthermore, social emotional development showed a positive correlation with physical activity (r = 0.19, p = 0.001) and a negative correlation with sedentary behavior (r = -0.17, p = 0.005). No significant correlations were observed between fundamental movement skills and sedentary behavior, or between different levels of physical activity. Conclusions. The findings suggest that improved fundamental movement skills contribute to enhancingsocial emotional development and increasing physical activity while reducing sedentary behavior. This study provides a valuable framework for promoting physical literacy and optimizing physical education practices.